A casa das bolsas - Cervo, Juliana Milman (2018)
The present thesis consists of two volumes: the novel The house of the handbags, and the critical theory essay on artistic creation named (In)jured covers. The research was inspired by the necessity of given voice to ancestors which live inside my body – especially my maternal grandmother, whose past had been marked by the overwhelming trauma of World War II. Considering the emptiness of a missing past, I formulate the following question: How is it possible to take on pre-birth memories? To do so, I deal with multiple verbal tenses and narrative voices in the fictional part in order to demonstrate gaps or to heal the wounds by filling in them imaginative spaces. Due to its synaesthetic feature, the critical essay gathers historical documents, photographs, films, diaries’ fragments, family texts, as well as conversations with patients which inspired the development of the novel. Furthermore, I carried out a thorough affective study on the vacuum that may last between generations with the purpose of stablishing not only a bond, but also a contact.